Determinants of Qris Reuse Intention Among Buyers and MSME Merchants in Banyumas Raya - Satria Candra Wibowo; Retnaningsih; Sendy Watazawwadu’Ilmi (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: QRIS (Quick Response Code Indonesian Standard) is a national digital payment initiative aimed at standardizing electronic transactions and enhancing financial inclusion. While QRIS adoption is growing nationally, significant disparities persist across regions, particularly among micro, small, and medium enterprises (MSMEs) in areas like Banyumas Raya.Purpose: This study aims to identify the key factors influencing users’ and MSMEs’ behavioral intention to continuously reuse QRIS in the Banyumas Raya region of Central Java.Design/methodology/approach: The research adopts a quantitative method based on the Technology Acceptance Model (TAM). Data was collected from 155 respondents (115 users and 40 MSMEs) using purposive sampling. Structural Equation Modeling using the SmartPLS software was employed to test the relationship between perceived ease of use, perceived usefulness, attitude toward use, and reuse intention.Findings/results: Perceived ease of use significantly influences both perceived usefulness and attitude toward using QRIS, while attitude toward using is the strongest predictor of reuse intention. Interestingly, perceived usefulness does not significantly affect attitude. Despite high user satisfaction, a gap remains between positive perception and actual reuse behavior, particularly among MSME merchants.Conclusion: Enhancing user experience and simplifying payment process are essential for sustaining QRIS usage.Originality/value (state of the art): This study provides novel insights into post-adoption behavior in digital payments, offering strategic implications for policymakers to improve financial inclusion through sustained QRIS usage in regional MSME ecosystems. Keywords:  digital payment, MSMEs, QRIS, reuse intention, technology acceptance